Study Literature Review of the Rise of Tax Avoidance Practices - Raya Puspita Sari Hasibuan; Iskandar Muda; Sambas Ade Kesuma (CV. Ridwan Publisher, 2023)
This study aims to find out how many companies are trying to avoid taxes. This research was conducted by observing a number of papers, namely by documenting various articles related to tax avoidance and then adapting them according to several categories until finally there were 313 articles that could be used. Initially there were 644 articles, then adapted based on the selection of abstracts and several inappropriate criteria so that the number became 404 articles, and then read again until finally there were 313 articles that could be examined. In this study, the fact is that many companies are trying to avoid taxes, utilizing the services of tax consultants in order to reduce the amount of corporate tax that must be paid. In addition, the company always tries to use a variety of very subtle techniques so that the tax authorities cannot find out, there is a very significant difference in relation to carrying out tax evasion by taking advantage of loopholes in the law compared to carrying out illegal tax evasion and this will certainly lead to new problem for the company. Thus, the urgency of paying taxes will always be supervised and monitored by the government due to certain targets in an effort to increase the realization of tax revenues every year.